Optimizing a standard preparation procedure for grain size analysis of marine sediments by laser diffraction (MS-PT4SD: Marine sediments-pretreatment for size distribution). (January 2021) - Jaijel, Roy; Goodman Tchernov, Beverly N.; Biton, Eli; Weinstein, Yishai; Katz, Timor
Abstract: Grain size distributions are a key physical measurement in marine sediment studies. The introduction of laser diffraction spectrometry analyzers a few decades ago, allowed the differentiating of grain size in higher resolution than before, and led to increased volumes of samples analyzed overall. However, pretreatment of the sediment samples is required for obtaining high quality results by this method. Currently there are different pretreatment methods for different sediments, but no inclusive, standard method that is applicable across many types. Moreover, often the particulars of the methods are not fully described in the literature. A standard simple and effective pretreatment method which is applicable for a large variety of marine sediments is required as it can allow for intra and inter study comparisons. This study systematically tested and compared commonly applied digestion and dispersion pretreatment techniques for particle size analysis by laser diffraction spectrometry. The pretreatments were applied on a wide spectrum of marine sediments to distill a single protocol that produces precise, reliable, and consistent results across all samples. The recommended marine sediment pretreatment protocol ('PT4SD') reduces the needed amount of sediment for analysis, reduces handler bias and overall digestion time. We propose that using 'PT4SD' as a standard pretreatment protocol will greatly benefit sedimentological laboratories individually, as well as encourage and improve the depth of cross-study comparability, thereby improving the collective field of marine sedimentology and related research as a whole. Highlights: Selection of a pretreatment procedure greatly affects grain size distribution spectra in laser diffraction analysis. An experimental matrix was used to distill a simple and efficient pretreatment for a wide range of marine sediments. The standard method suggested is precise, accurate, relatively quick and minimizes 'handler error'. The marine sediments tested represent different depositional environments from estuary to deep sea. A wide use of the suggested protocol will enable inter and intra study comparison within and between laboratories.